Evaluation of the Conformity of Marine Spatial Utilisation Activities (KKPRL) for Ports Sector in Palu Bay Indonesia - Ahmadi, Nurdin; Suharyanto, Suharyanto; Prasetiyo, Didit Eko; Rahmawati, Yeni; Ndricenning, I Mario; Sidqi, Muhandis; Jakasukmana, Munandar; Syahruddin, A; Bakri, Reza Fauzi; Hafid, Wahyu; Salasah, Rosmawati; Nasution, Syahrial (Politeknik Kelautan dan Perikanan Dumai, 2024)
The utilization of marine space requires regulation due to the multidimensional and overlapping interests in maritime areas. The increasing demand for marine space for various commercial and non-commercial purposes necessitates sustainable management strategies and legal governance to reduce cumulative impacts on the marine environment. The compliance level of marine spatial utilization activities (MSUA), particularly in port activities, is determined by three aspects: the extent realization aspect, the type of activities aspect, and the legal subject aspect. Progress in licensing and meeting MSUA obligations is evaluated using a matrix of suitability indicators with weighting and assessment for each indicator. The research findings indicate that, concerning the extent realization aspect used in the studied ports, compliance with the given MSUA is still observed. However, for the type of activities aspect and the legal subject aspect, progress in licensing and meeting MSUA obligations has not been fully adhered to. Thus, overall compliance is at a level of adherence with notes. Furthermore, at the business compliance level, operations are not conducted properly, as changes in status from non-commercial to commercial activities are not reported, potentially resulting in the loss of non-tax national revenue (PNBP). Regarding MSUA obligations, the indicators posing obstacles to compliance at ports are those related to the obligation of submitting written reports annually to the Minister of Maritime Affairs and Fisheries and reporting the establishment and/or placement of buildings and installations at sea to the agency responsible for hydrographic and oceanographic government affairs.